2008
DOI: 10.1590/s0006-87052008000100020
|View full text |Cite
|
Sign up to set email alerts
|

Caráter stay-green e produtividade de grãos em trigo

Abstract: ); GUILHERME RIBEIRO ( 3,6 ); CYRANO CARDOSO BUSATO ( 3 ) RESUMOO caráter stay-green é um dos fatores que poderá auxiliar o melhorista na obtenção de plantas mais produtivas, devido à permanência verde por um período mais prolongado favorecendo o enchimento de grãos. Desta forma, o objetivo do trabalho foi o de avaliar o desempenho de diferentes constituições genéticas de trigo com e sem a presença do caráter stay-green e verificar se a expressão de alelos que intensificam a coloração verde por um período… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…The estimate of h 2 for grain yield was > 56% in all cases, a rate considered relatively high (Silva et al 2008). For plant height, the lowest estimate was > 64%, and for flowering > 85% (Table 2).…”
Section: Cycle I Cycle Stagesmentioning
confidence: 86%
“…The estimate of h 2 for grain yield was > 56% in all cases, a rate considered relatively high (Silva et al 2008). For plant height, the lowest estimate was > 64%, and for flowering > 85% (Table 2).…”
Section: Cycle I Cycle Stagesmentioning
confidence: 86%
“…Abiotic stress tolerance is a major feature of stay-green genotypes, giving stability to grain yield even in unfavorable environmental conditions (SILVA et al, 2008). Superiority of grain yield in staygreen lines when compared to synchronized sibling lines, was especially restrictive in environmental conditions such as low rainfall at the end of the cycle (LUCHE et al, 2013).…”
Section: Application Of the Stay-green Character In Plant Breedingmentioning
confidence: 99%
“…Stay-green is the term given to a variant in which senescence is delayed in comparison to a standard reference genotype (THOMAS; HOWARTH, 2000;JOSHI et al, 2007). The stay-green character is characterized by a longer green state of the plant in the late period of grain filling, establishing a senescence pattern in which leaves and stem are the last parts to loose photosynthetic ability, providing greater production of sugars from photosynthesis (SILVA et al, 2008). Based on the increase of grain filling ability and improvement of desirable traits, it is suggested that the character results in yield gains.…”
Section: Introductionmentioning
confidence: 99%
“…In southern Brazil, a significant contribution of stay-green trait for grain yield and abiotic stresses tolerance has been observed (Luche et al 2013). The low complexity of stay-green i.e., its reduced number of genes can facilitate the breeder's work incorporate into elite genotypes, besides the great contribution involving high additive effects on inheritance (Joshi et al 2007), a condition that favors the selection pressure in early generations in achieving significant genetic gains (Silva et al 2008a).…”
Section: Introductionmentioning
confidence: 99%